ANALISIS PENGARUH NIM, NPL, BOPO, BI RATE DAN CAR TERHADAP PENYALURAN KREDIT BANK UMUM GO PUBLIC PERIODE TAHUN 2012-2016 - Haryanto, Satrio B.; Widyarti, Endang Tri (Faculty of Economics and Business Diponegoro University, 2017)
Banks as an intermediary institution have an important role to improve the public welfare in accordance with the mandate of the Act. Loan distribution is the bank's main activity as well as the realization as an intermediary institution.This research used internal and external factors as independent variable and loan growth as dependent variable. Number of samples used by researchers are 23 Commercial Banks. Period used in this research is 2012-2016. The method of analysis used in this research model is multiple linear regression.The result of the research shows that Net Interest Margin (NIM) has a significant and positive impact on loan distribution, Operating Expense to Operating Income (BOPO) has a significant and negative impact on loan distribution. While the Non Performing Loan (NPL), BI Rate, and Capital Adequacy Ratio (CAR) have no significant effect on loan distribution.